Evaluasi Tingkat Kemampuan Kardiovaskuler Atlet Arung Jeram Mapala Universitas Gunung Leuser Aceh - Afrizal Afrizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the level of cardiovascular ability of the Mapala white water rafting athletes at Gunung Leuser University, Aceh in 2022. This study is a descriptive study. The instrument used is a cardiovascular test using a 12-minute run test. The sample in this study consisted of 15 athletes from 21 populations. The data analvysis technique used in this study was descriptive statistics with the percentage formula. The results of the research on the cardiovascular ability of white water rafting athletes at the University of Gunung Leuser Aceh using a 12-minute running test had an average value of 2223.67 meters at the medium category level. The percentage of cardiovascular ability level of rafting athletes at Mapala Gunung Leuser Aceh University with a percentage of 2 athletes in the very good category (13.33%), 5 athletes in the good category (33.33%), 4 athletes being in the moderate category (26, 67%), 3 athletes were in the poor category (20.00%), and 1 person was in the very poor category (6.67%). Based on the results of research, the level of cardiovascular ability of the mapala white water rafting athletes at Gunung Leuser University, Aceh in 2022 is in the medium category.